Avian Immunology - Schat, K. A. (Karel Antoni), 1944-; Kaspers, Bernd; Kaiser, P. (Pete) (Elsevier/Academic Press, 2014)
Provides an up-to-date overview of the current knowledge of avian immunology. From the ontogeny of the avian immune system to practical application in vaccinology, this book encompasses all aspects of innate and adaptive immunity in chickens.